Internet som tekstsamling og resourcebank i sprogundervisning - Møller, Bernt (HERMES - Journal of Language and Communication in Business, 2003)
The World Wide Web contains huge amounts of documents in several languages. Also, internet offers numerous resources which may help in finding and understanding web documents. This article firstly aims at passing on facts and considerations from the author’s teaching experience within a thematic process framework of Information Management. Here, information searching, evaluation, registration and presentation are guide-lines. In information searching, the points touched upon include search engine strate-gies, such as qualified URL guessing and language checking. Information evaluation mentions a few basic techniques while information registration and presentation point to the utility of co-integrating multimedia links in the software applications. Secondly, the article in a smaller section suggests a typology for internet language resources and comments on a number of useful language web sites. Finally, selected perspectives and challenges are outlined.